Dosis de gallinaza y su influencia en las características agronómicas y rendimiento de Apium graveolens L. “APIO”, Zungarococha-Loreto. 2019 - Jaramillo Dorado, Jose Arturo (2024)
The study was related to determine the influence of different doses of poultry manure on Apium graveolens L., celery where its agronomic characteristics and yield were evaluated and in this way investigate how the doses of poultry manure affected the crop: The place of the study was in the Faculty of Agronomy, Zungarococha, where the statistical management was with the DBCA, the ANOVA and the Tukey Test. The doses of poultry manure were in t/ha, as follows: T1:30; T2:40; T3:50 and T4: 60, whose results were observed at the time of harvest at 5 months in which T4 presented the best results of the experiment obtaining a yield of 26,067 Kg/ha and S/.109,853 of utility.